DEVELOPING BATIK-BASED BRIDE CLOTHES DESIGN WITH JAVANESE SCRIPT MOTIFS - Intan Wulansari; Timbul Subagya (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2024)
The selection of Javanese alphabet as a theme of artwork motive creation is intended to introduce and preserve Indonesian cultures through artwork. There are three objectives of this artwork creation. First, creating handmade batik motive design in the form of Javanese alphabet style. Second, creating new design of Javanese blouse. Third, applying handmade batik motive derived from Javanese alphabet to the Javanese blouse. Data for analysis was collected through literature review and field exploration. The art creation method of SP. Gustami was used for creating the artwork which consists of three steps, namely exploration, design and embodiment. As a result, we managed to create four handmade batik motives in the form of Javanese alphabet style. Each motive was given a title according to its characteristics, namely Puspa Nala, Puspa Kara, Puspa Hayu, and Puspa Jawi. Finally, it can be concluded that this art creation produces innovation in the form of handmade batik motives derived from Javanese alphabet and applied for the Javanese blouse